TECHNICAL EQUIPMENT AS A DIRECTION OF DEVELOPMENT OF PUBLIC ADMINISTRATION AT THE MODERN STAGE - Oleh Bilyk; Olena Zharovska (Публічне управління та регіональний розвиток)
In the article summarizes the transformations that affect public administration due to the equipment of spheres, environments, spaces and structures with technical means, which are characterized by wide volumes of functional capacity. The degree of development of e-government is studied, where Ukraine has a proper position due to the creation and expansion of applications, automated platforms in information and communication technologies, increasing the prevalence of such complexes as the Internet of Things and SMART technologies. The evolution of the development of technical equipment for the implementation of executive functions and regulatory actions based on initiated measures to maintain law and order and social norms is clarified, where foreign experience is considered. The methodological justification of the level of development of public administration according to the relevant criteria that underlie the trends in the technical equipment of the subordinate environment, which measures the level of digital transformation of the regions of Ukraine, is highlighted. It is proved that in comparison with global trends, our state has a perfect appearance and occupies a proper place in such a technological breakthrough. Ranking according to the criteria of regional development of Ukraine has been established, which determines the technical equipment of subordinate spheres and spaces, as a result of which it has been revealed that public administration as a whole is reaching a qualitatively new level. It has been substantiated that by increasing the level of digital transformation of the regions of Ukraine, the institutional capacity of structural units is manifested not only in terms of individual territories and those spheres and spaces that are in them, but also of the state as a whole. Proposals have been developed to systematize and systematically reflect the features of the equipment with technical means of subordinate and subordinate spheres, spaces, and environments using methodological foundations intended for this purpose, since this is clearly related to the development of public administration.